Safety aspect in intelligent buildings / Marlina Ramli - Ramli, Marlina (Faculty of Architecture, Planning and Surveying, 2010)
The intelligent building concept was introduced in United States in the early 1980’s. Currently has many buildings in Malaysia are using this concept, especially in the high rise office building. We know the installation or use of these systems require a very high cost and expensive. Therefore, I want to know whether Intelligent building systems in office buildings in Malaysia is very useful, or it is just a waste. The chapters in this study were arranged in six chapters. It was introduction, literature review, methodology, case studies, finding & analysis and last with conclusion & recommendation in chapter 6. There were three objectives in the research. The source on the study was used primary and secondary data. The instrument use in conducting a survey is questionnaire to public, user technical group and interview. The objective in this dissertation is to find out the effectiveness of intelligent building system at high rise office building compared to non intelligent building in term of the safety aspect. Safety systems in buildings are very important to ensure those occupants are in a safe. What I want to know is, whether the safety system in the Intelligent Building provides a very useful and benefit to the occupants when compare with non intelligent building. The second objective is to find out the cost of operating, maintenance and the replacement equipment for intelligent building system. The high cost of maintenance, whether the system returns the worth the benefits received by residents balanced with the money that was invested. The third objective is to give recommendation for a better and optimally used building intelligent system, the recommendation is proposals are contained in the chapter six and proposed by the technical group and also the results of interviews with the local authority.